Influence of weave structure on mechanical properties of cotton fabrics reinforced with unsaturated polyester (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
The effect of weave structure on the mechanical properties of cotton fabric reinforced with unsaturated polyester (UP) resin has been studied. Cotton yarns are woven into four weave structures (plain 1/1, rib 4/4, twill 3/1 and satin 5/2 weaves) on a tappet loom. Fabrication of the composite is done using the hand lay-up technique. Results show that the twill fabric has an optimal strength of 15.21 MPa, while satin fabric shows the least tensile strength of 11.31MPa. The tensile and flexural strengths of the composites are improved by 47–140% and 44–49% when compared with neat polyester resin respectively. Composite with twill fabric shows the best tensile and flexural strengths of 48 MPa and 73.2 MPa, a tensile modulus of 0.37 GPa and elongation-at-break of 52.8%, which is closely followed by plain, rib and satin weave composites. Charpy impact test shows that the twill fabric composite absorbs more energy followed by the plain, rib and satin fabric composites. Moreover, the characterization of the composites evaluated by SEM and FTIR shows better bonding of treated fabric with the hydrophobic polyester and the presence of functional groups respectively.